2004
DOI: 10.1021/jm031018y
|View full text |Cite
|
Sign up to set email alerts
|

Arylcyanoguanidines as Activators of Kir6.2/SUR1KATP Channels and Inhibitors of Insulin Release

Abstract: Phenylcyanoguanidines substituted with lipophilic electron-withdrawing functional groups, e.g. N-cyano-N'-[3,5-bis-(trifluoromethyl)phenyl]-N' '-(cyclopentyl)guanidine (10) and N-cyano-N'-(3,5-dichlorophenyl)-N' '-(3-methylbutyl)guanidine (12) were synthesized and investigated for their ability to inhibit insulin release from beta cells, to repolarize beta cell membrane potential, and to relax precontracted rat aorta rings. Structural modifications gave compounds, which selectively inhibit insulin release from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Tagmose et al [77] found that the replacement of the pyridine ring in pinacidil with a 3,5-disubstituted phenyl group yielded compounds which activate β-cell K ATP channels at concentrations which do not relax smooth muscle. β-Cell activity of the compounds was shown to depend on size and bulkiness of the N-alkyl side chain.…”
Section: Prototypementioning
confidence: 99%
“…Tagmose et al [77] found that the replacement of the pyridine ring in pinacidil with a 3,5-disubstituted phenyl group yielded compounds which activate β-cell K ATP channels at concentrations which do not relax smooth muscle. β-Cell activity of the compounds was shown to depend on size and bulkiness of the N-alkyl side chain.…”
Section: Prototypementioning
confidence: 99%
“…Arylcyanoguanidines with short aliphatic side chains (e.g. N -aryl- N' -cyano- N'' -alkyl-guanidines) are known as activators of ATP-sensitive potassium channels and inhibitors of insulin release from beta cells, but small structural changes can dramatically change the efficacy [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Piperidinone derivatives act as potential inhibitors of human placental aromatase in vitro (Baroudi et al, 1996). In particular, N-cyano compounds have been found as activators of ATP-sensitive potassium channels and inhibitors of insulin release (Manley et al, 1993;Tagmose et al, 2004;Yoshiizumi et al, 1997). This has prompted us to carry out accurate determinations of the crystal structures of a host of N-cyano-substituted piperidinone derivatives.…”
Section: Commentmentioning
confidence: 99%